Design and Performance of Nonlinear Control for an Electro-Hydraulic Actuator Considering a Wearable Robot - Buchun Song (Processes, 2019)
In the development of a wearable robot, compact volume size, high energy efficiency, and a high load capacity linear actuator system are necessary. However, conventional hydraulic actuator systems are difficult to apply to wearable robots. Also, they have nonlinearities because of the presence of hydraulic fluid in a single rod cylinder. Electric linear actuators resolve the problems of hydraulic systems. However, due to their low load capacity, they are not easy to apply to wearable robots. In this paper, a pump-controlled electro-hydraulic actuator (EHA) system that considers the disadvantages of the hydraulic actuator and electric actuator is proposed for a wearable robot. Initially, a locking circuit design is considered for the EHA to give the system load holding capacity. Based on the developed model, the adaptive sliding mode control (ASMC) scheme is designed to resolve the nonlinearity problem of changes in the dynamic system. The ASMC scheme is then modeled and verified with Simulink. In order to verify the performance of the proposed adaptive control with the model, experiments are conducted. The proposed EHA verifies that the ASMC reaches the target value well despite the existence of many model uncertainties.